2004
DOI: 10.1007/s00127-004-0826-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing compulsory admission in first-admitted subjects with psychosis

Abstract: These results suggest that factors related to the disease itself play an important role in decisions concerning compulsory admission. The high frequency of compulsory admission as the first mode of contact with psychiatric hospital in subjects with psychosis constitutes a major public health issue. Further research on the strategies aimed at avoiding compulsory admission in subjects with incipient psychosis is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
3
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 26 publications
6
33
3
1
Order By: Relevance
“…The strategy of identifying who was most instrumental in ending the search for psychosis‐indicated interventions differs from studies that reported extensively on first or total contacts . Whereas these studies concluded that family physicians were critical agents to assist in reducing delay, educational efforts regarding psychosis, substance use and treatment resources may need to be focused more directly at families and community professionals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strategy of identifying who was most instrumental in ending the search for psychosis‐indicated interventions differs from studies that reported extensively on first or total contacts . Whereas these studies concluded that family physicians were critical agents to assist in reducing delay, educational efforts regarding psychosis, substance use and treatment resources may need to be focused more directly at families and community professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of identifying who was most instrumental in ending the search for psychosis-indicated interventions differs from studies that reported extensively on first or total contacts. 4,32,35 Whereas these studies concluded that family physicians were critical agents to assist in reducing delay, educational efforts regarding psychosis, substance use and treatment resources may need to be focused more directly at families and community professionals. Our findings corroborate the importance of relatives in ending treatment delay 34,35 and that parents need support to overcome both patients' reluctance to go for help and those obstacles to access attributable to professional caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involuntary treatment may thus be warranted to avert risk of suicide, treating a life‐threatening medical condition, aggressiveness or to facilitate insight into the disease, to consequently accept the necessity of treatment. Especially, substance abuse, lack of insight and male sex seems to increase the risk of involuntary admission .…”
Section: Introductionmentioning
confidence: 99%
“…The use of involuntary treatment in psychiatry is highly controversial and has been extensively debated . Essential of this discussion is the issue of loss of autonomy versus necessity of treatment both from society and patient's health points of view.…”
Section: Introductionmentioning
confidence: 99%